PENGARUH DINAMIKA LINGKUNGAN, KEMAMPUAN MANAJEMEN DAN STRATEGI BISNIS TERHADAP KINERJA PERUSAHAAN PT. PLN KOTA BANJARMASIN - Widyanti, Rahmi .; Maskur, Maskur; Basuki, Basuki; Azahraty, Azahraty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Objective of this study was to examine and analyze the effect of Environment dynamic, Management Ability and Business Strategics on Corporate performance of PT PLN (Persero) UP3 Banjarmasin. This research using the method is explanatory research with a quantitative approach. Variables are measured using a Likert scale and data collection with questionare as research instrument. The sample in this study were 46 employees of PT PLN (Persero) UP3 Banjarmasin from a total population of 80 people. Data processing in this study using SPSS software version 25, with descriptive analysis and multiple regression analysis hypothesis testing. The results this study showed that: (1) Environment dinamic had a positive and significant effect on the corporate performance of PT PLN (Persero) UP3 Banjarmasin as evidenced by the t-count of 2.202. (2) Management ability has a significant effect on the corporate performance of PT PLN (Persero) UP3 Banjarmasin, as evidenced by the t-count value of 2,534. (3) Business Strategics has a significant effect on the corporate performance of PT PLN (Persero) UP3 Banjarmasin, as evidenced by the t-count value of 2,534. 4) Simultaneously, the variables of training and human resource development have a significant effect on the performance of employees of PT PLN (Persero) UP3 Banjarmasin as evidenced by the value of F-count = 39,164.